Material digital para el aprendizaje en el área de estudios sociales con los estudiantes de séptimo año de educación intercultural bilingüe, en la unidad educativa intercultural bilingüe Surupucyu, parroquia Guanujo, cantón Guaranda, provincia Bolívar en el año lectivo 2023-2024 - Cevallos Cabezas, Mirella Estefania (2024)
The study "Digital Material for Learning in the Area of Social Studies with Seventh Grade Students of Intercultural Bilingual Education at Surupucyu Intercultural Bilingual Educational Unit, Guanujo Parish, Guaranda Canton, Bolívar Province in the Elective Year 2023-2024" was carried out with the aim of promoting interactivity for the development of meaningful learning with seventh-grade students in the area of social studies through digital material. A mixed approach was employed, combining quantitative and qualitative elements to obtain a comprehensive understanding of the topic. The research focused on 26 seventh-grade students from Surupucyu Educational Unit and was conducted under a non-experimental, descriptive design. The methods used included bibliographic analysis, logical-historical, and deductive- inductive approaches. These approaches allowed for the exploration of relevant literature, examination of historical context, and logical and deductive analysis of information. The findings revealed that traditional teaching methodology predominated in the studied educational environment, with a teacher-centered approach and limited use of digital resources. However, a positive interest was identified among students towards the integration of digital material in the learning process.